Benign Prostatic Hyperplasia – An economic assessment of fixed combination therapy based on a literature review - Roberto Messina; Vincenzo Mirone (Archivio Italiano di Urologia e Andrologia, 2015)
FederAnziani Senior Italia and SIU – Italian Society of Urology – have decided to work together to draft a document focussing on Benign Prostatic Hyperplasia (BPH), and to stress the importance of adherence with pharmacological treatment in this setting, from both a scientific and a patient standpoint. Starting from a literature search, the two associations analysed to what extent an increase in treatment adherence amongst these patients influences hospital savings and to what extent therapy persistence levels are affected by monotherapy rather than free drug combinations. These estimates were performed only on patients taking medicinal products belonging to the 5 α-reductase inhibitors (5ARI) class that, although not indispensable, are the compounds that bring the greatest benefits, especially in the elderly and for which we know that every additional 30 days of therapy reduced the likelihood of acute urinary retention (AUR) and surgery by 14% and 11% respectively *. The results show that the use of fixed combination therapy would involve an increase in persistence due to the lower rate of patients abandoning treatment over time. Each 30 day-increment of 5ARI therapy, i.e. for an expenditure of 10.6 million euros extra per year for 5ARI medication, savings of approximately 24.3 million euros in hospital costs could be achieved.